Examination of Customers Intention to Adopt Digital Banking Services: Moderating Role of Perceived Risk in Banking Sector of Pakistan during COVID-19 (Journal of Social Sciences Review, 2022)
The COVID-19 pandemic poses a huge challenge for the Pakistani financial industry, leading to an increase in digital banking as it has become a necessity for users of financial services. The research seeks to empirically test the impact of customer perceptions on the adoption of digital banking during COVID-19. In addition, this study investigates the impact of performance expectancy, Effort Expectancy, and Social influence on customer’s intentions to adopt digital banking services with moderating effect of perceived risk. The population of the study consist of all the customers of banks which are providing digital banking services in Pakistan. A survey was conducted and 254 responses were analyzed with the help of structural equation modeling. Study concludes that Performance Expectancy, Effort Expectancy and  Social Influence as independent variable and Perceived Risk as moderating variable has a significant impact on the perception of customers of digital banking  applications. Study further contributes that Perceived Risk moderates the relationship between Performance Expectancy, Effort Expectancy, Social Influence and the intention of customers of digital banking applications to adopt digital banking services.
Keywords: Digital Banking Services; Banking Sector; UTAUT; Perceived Risk; Performance Expectancy; Effort Expectancy